2019
DOI: 10.1371/journal.pone.0214143
|View full text |Cite
|
Sign up to set email alerts
|

Parenting practices that may encourage and discourage physical activity in preschool-age children of Brazilian immigrant families: A qualitative study

Abstract: Brazilians are a rapidly increasing Latino immigrant group in the United States (US), yet little research has examined factors influencing physical activity (PA) levels and behaviors of children growing up in Brazilian immigrant families. This information is needed to develop culturally sensitive interventions tailored to this population. Therefore, this qualitative study explored PA parenting practices used by Brazilian immigrant mothers living in the US. Thirty-seven Brazilian immigrant mothers with at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 66 publications
(107 reference statements)
3
27
0
Order By: Relevance
“…In the present study, active play was found to be associated with time spent with family and peers in all age groups. It supports the idea that the family and peers is an important factor for enhancing physical activity in children and youths [7][8][9][10]. A strategy for increasing active play and time spent with family and peers combined with a lessening in sedentary behavior may Table 1 Baseline of physical activity and creativity fight against the problems of an increasing physical inactivity and sedentary behavior and support health promotion in children and youths.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In the present study, active play was found to be associated with time spent with family and peers in all age groups. It supports the idea that the family and peers is an important factor for enhancing physical activity in children and youths [7][8][9][10]. A strategy for increasing active play and time spent with family and peers combined with a lessening in sedentary behavior may Table 1 Baseline of physical activity and creativity fight against the problems of an increasing physical inactivity and sedentary behavior and support health promotion in children and youths.…”
Section: Discussionsupporting
confidence: 55%
“…The result thus reflects that association in each age group in which their cognitive and physical functions are different. In addition, this study pointed to the physical activity indicators, including active play, time with family and peers, and sedentary behavior which has been frequently reported to affect physical activity and physical fitness in children and youth [5][6][7][8][9][10]. The results showed that creativity was associated with active play in adolescents; however, the association was not found in participants aged 6-14 years.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…There are both similarities and differences when comparing qualitative evidence of parent perspectives on preschoolers' movement and dietary behaviours from other settings to the findings from Soweto. A recent study examined such parenting practices in Brazilian immigrant families in the USA (51) . The Brazilian parents actively discouraged screen time in favour of physical activity and set boundaries in a more health-centred manner than the Sowetan parents, who mostly restricted screen time for more pragmatic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…As for parents, according to a report by the Child Welfare League Foundation, many Taiwanese children don't get sufficient exercise, mainly due to poor air quality, parents' lack of time, lack of suitable facilities, and safety concerns [26]. Similarly, Fjortoft, Pedersen, Sigmundsson, and Vereijken assert that due to the prevalence of automobiles, these days few children walk or bike to school [27] and that for both parents and children physical and outdoor activity is increasingly being replaced by less physical indoor activities such as internet browsing, playing video games, and watching television [28]. As for schools, even though preschools typically schedule 30 minutes per day of rigorous exercise, for many teachers this means any physical activity whatsoever, such as playing tag or playing with musical toys [29].…”
Section: Discussionmentioning
confidence: 99%